2023
DOI: 10.3390/molecules28124850
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potent Inhibitors Targeting EGFR and HER3 for Effective Treatment of Chemoresistance in Non-Small Cell Lung Cancer

Abstract: Non-small cell lung cancer (NSCLC) is the most common form of lung cancer. Despite the existence of various therapeutic options, NSCLC is still a major health concern due to its aggressive nature and high mutation rate. Consequently, HER3 has been selected as a target protein along with EGFR because of its limited tyrosine kinase activity and ability to activate PI3/AKT pathway responsible for therapy failure. We herein used a BioSolveIT suite to identify potent inhibitors of EGFR and HER3. The schematic proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Subsequently, the highly potent inhibitor was subjected to standard docking within the chosen binding site. The optimal conformation was determined by assessing the lowest binding energy of the ligand in the docked complex …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the highly potent inhibitor was subjected to standard docking within the chosen binding site. The optimal conformation was determined by assessing the lowest binding energy of the ligand in the docked complex …”
Section: Methodsmentioning
confidence: 99%
“…The optimal conformation was determined by assessing the lowest binding energy of the ligand in the docked complex. 42 …”
Section: Methodsmentioning
confidence: 99%
“…All these binding sites were evaluated individually to analyze the binding of potent inhibitors, and it was found that the second binding site (dark pink) was the optimum druggable binding site for pyrazole containing sulfonamide derivatives ( Ibrar et al, 2016 ). Thence, the potent inhibitors were docked in the selected binding site via standard docking, and the best pose was selected based on the lowest binding energy and highest binding affinity ( Dera et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%